Theories and methods for studying online communities for people with disabilities and older people - Pfeil, Ulrike; Zaphiris, Panayiotis (My University, 2009)
This chapter discusses the importance of online communities for people with disabilities and the elderly. It points to a number of weaknesses of existing text based computer mediated communication (CMC) applications, but also highlights some of the key benefits of CMC for these special groups of users. The key theoretical foundations of CMC research are then covered in detail, explaining how those could help in studying online social interaction of people with special needs. This chapter points out the fact that there is valuable existing research in the domain of theoretical CMC but highlights the weakness up to now in applying it to the study of online communities for people with special needs.
Keywords: Online communities; CMC theory; Online social interaction; Online research methods